Approach or Avoidance? The Mechanisms Underlying the Impact of Community Goal Orientation on Residents’ Waste Separation Recycling Behaviors - Zhihao Wang; Lingchao Huang; Wei Li; Duo Xu (Behavioral Sciences)
Amidst the vigorous pursuit of sustainable development, the significance of community management has become increasingly evident. This study, anchored in goal orientation theory, delineated a conceptual model that elucidated the influence of community goal orientation on residents’ waste separation recycling behaviors. Utilizing a longitudinal study design combined with self-report methods, data comprising 871 paired observations from 166 residents were collected and analyzed via multilevel structural equation modeling to test the proposed hypotheses. The findings corroborated that the community approach goal orientation not only had a direct positive impact on the residents’ waste separation and recycling behaviors but could also induce the residents’ environmental passion and subsequently influence their waste separation and recycling behaviors. Conversely, community avoidance goal orientation exhibited no significant effect on either the environmental passion or waste separation recycling behaviors. Furthermore, the community trust was found to positively moderate the effect of community approach goal orientation on the environmental passion. Meanwhile, the community trust moderated the mediating role of environmental passion. However, the community trust did not moderate the effect of the community avoidance goal orientation on environmental passion.